X-chromosome inactivation patterns in monozygotic twins and sib pairs discordant for nonsyndromic cleft lip and/or palate - Kimani, Jane W.; Shi, Min; Daack-Hirsch, Sandra; Christensen, Kaare; Moretti-Ferreira, Danilo; Marazita, Mary L.; Field, L. Leigh; Canady, John W.; Murray, Jeffrey C. (Wiley-Blackwell, 2007)
Nonsyndromic clefts of the lip and/or palate are common birth defects with a strong genetic component. Based on unequal gender ratios for clefting phenotypes, evidence for linkage to the X chromosome and the occurrence of several X-linked clefting syndromes, we investigated the role of skewed X chromosome inactivation (XCI) in orofacial clefts. Our samples consisted of female monozygotic (MZ) twins (n = 8) and sister pairs (n = 152) discordant for nonsyndromic clefting. We measured the XCI pattern in peripheral blood lymphocyte DNA using a methylation based androgen receptor gene assay. Skewing of XCI was defined as the deviation in inactivation pattern from a 50:50 ratio. Our analysis revealed no significant difference in the degree of skewing between twin pairs (P = 0.3). However, borderline significant differences were observed in the sister pairs (P = 0.02), with the cleft lip with cleft palate group showing the most significant result (P=0.01). We did not find evidence for involvement of skewed XCI in the discordance for clefting in our sample of female MZ twins. However, results from the paired sister study suggest the potential contribution of skewed XCI to orofacial clefting, particularly cleft lip and palate. (C) 2007 Wiley-Liss, Inc.
Keywords: cleft palate; cleft lip; X inactivation; monozygotic twins; discordant